Evaluación de diferentes densidades de siembra con el método al voleo, de la línea promisoria L- 17 de arroz (Oryza sp) en la localidad de Babahoyo” - Silvera Avilés, Yessy Waleska (2025)
Rice is the staple food for half of the world's population and the second most produced cereal globally, surpassed only by maize and wheat. In Ecuador, it is an essential food, with an average consumption of 50 kg per person per year. The provinces of Guayas and Los Ríos lead its production, with an annual yield of approximately 778,680 metric tons of milled rice. However, declines in yield cause significant economic losses for farmers.This study aimed to evaluate the agronomic and productive performance of the promising rice line L-17 compared to the commercial variety SFL-11 on the fields of Agronomist Wellington Rodríguez in the canton of Babahoyo, Los Ríos province. The research was conducted using six treatments, each with three replications, at different planting densities for both the L-17 line and the commercial SFL-11 variety.A completely randomized block design (DBCA) was used with subdivided plots of 25 m² (5m x 5m). Statistical analysis was carried out using the InfoStat 2020 software (ANOVA), and the Tukey test was applied to evaluate key variables such as plant height, number of tillers, panicles, grain width and length (with and without husk), vigor, population, and the number of plants per square meter. The SFL-11 cultivar showed the highest number of tillers, with a measurement of 618.06, surpassing the L-17 cultivar, which recorded a lower value of 552.83 in comparison with the other line. Treatment 3 of the L-17 line achieved the highest profitability percentage, with 24.28%, while in the control (SFL-11), Treatment 5 obtained a profitability of 15.27%